Types of government deficit in respect of fiscal decision-making - Przybylska-Mazur, Agnieszka (Rodzaje deficytu budżetowego w aspekcie podejmowania decyzji fiskalnych, 2018)
Fiscal policy includes the government decisions on the size of taxes that affect the size of the government deficit. There are different types of government deficit. The aim of the analyses is to examine the relation between the type of deficit and the optimal level of tax rate. In this article we verify the hypothesis that the type of deficit considered affects the tax rate. For the hypothesis verification, we use the feedback rules that are the solution of the quadratic-linear problem
Financial Sciences. Nauki o Finansach, 2018, vol. 23, no. 2, s. 60-74
Keywords: deficit; tax rate; feedback rule; quadratic-linear problem; deficyt; stopa podatkowa; reguła sprzężenia zwrotnego; problem kwadratowo-liniowy